Pengaruh Penggunaan Video Animasi Terhadap Hasil Belajar Siswa Kelas XI MIA - Tangkal, Sisilia Febriyanti; Nurlia, Nurlia; Samaduri, Alwia (Jurnal Biologi Babasal, 2024)
This research aims to determine the effect of using animated video media on the learning outcomes of class XI MIA nervous system material at SMA Katolik Santo Yoseph Luwuk. This research is a type of quasi-experimental research which involves two classes with different treatments, namely the control class and the experimental class. The research design is pre-test and post-test one group. This research was carried out in the Even Semester of the 2023/2024 academic year at SMA Katolik Santo Yoseph Luwuk. The sample in this study consisted of two classes, namely class XI MIA 2 students as the experimental class and class XI MIA 1 students as control class. The data collection used in this research is a test technique in the form of questions pre-test and post-test in multiple choice form totaling 15 items. The data analysis technique is hypothesis testing using the t-test formula (t-test). Based on the research results, the t value was obtainedcount > ttable (4.152 > 2,02) eye H0 rejected while H1 accepted so that it can be concluded that there is an influence of the use of animated video media on student learning outcomes in class XI MIA nervous system material at SMA Katolik Santo Yoseph Luwuk.